Evaluación preliminar de lesiones físicas en cerámica Tallán museo de Tangarará 2023 - Gonzalez Espino, David (2024)
Preventive conservation is presented as a specific action that intervenes in identifying the physical injuries suffered by ceramic pieces of a pre-Hispanic nature. It was determined that there is no evaluation of the state of the physical injuries in the Tallán ceramics in the Tangarara Museum, a fact that prompts us to carry out investigations. The objective of the work was to develop a preliminary evaluation of the physical injuries that are located in the ceramic pieces of the Tallán culture that are in the possession of the Museum of Archeology and History of Tangarará. Methodology using 10 ceramics, surgical gloves, surgical masks, distilled water, swabs, and cards, research approach was quantitative, basic type, and non-experimental design. As results we have physical injuries that translate into fractures, holes, erosions, defects and imperfections. We identified scores above the upper control limit of 53.28, a fact that warrants intervention on the pieces. Therefore, it is pertinent to carry out a conservation evaluation on a quarterly basis to avoid physical injuries to the ceramic pieces.